'Informed Seeing': Reading the Seventeenth-Century Embroidered Cabinet at Milton Manor House through its Historical and Social Contexts. (2nd January 2016) - Pullan, Amanda
Abstract : This object lesson examines a seventeenth-century cabinet, held at Milton Manor House in Oxfordshire, which has been embroidered with biblical scenes. Starting from the premise that knowledge informs seeing, this article provides a close reading of the cabinet's iconography and historical context in order to highlight the knowledge — both the general ideologies and the individual interpretation — that may have informed its production. Through a detailed reading, the maker's negotiation of the virtue of submissiveness, a major tenet of women's education in the period, is identified as a possible theme.